A new species of Zeanichnus Jałoszyński in New Zealand (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł; Kołodziejczyk, Natalia (Zootaxa, 2015)
A new species of the cyrtoscydmine genus Zeanichnus Jałoszyński, Z. aupourianus sp. n. is described. This third representative of Zeanichnus is known to occur in the northernmost tip of North Island, New Zealand. Comparative notes on diagnostic characters are given, and the male copulatory organ of the new species is illustrated.